Cretaceous to Eocene mixed turbidite-contourite systems offshore Nova Scotia (Canada): Spatial and temporal variability of down- and along-slope processes. (April 2022) - Rodrigues, S.; Deptuck, M.E.; Kendell, K.L.; Campbell, C.; Hernández-Molina, F.J.
Abstract: The identification of several Cretaceous to Paleogene mixed turbidite-contourite systems along the upper to middle continental slope of Nova Scotia provides a unique opportunity to investigate the spatial and temporal variability of their morphological elements. The mixed systems were studied using 3D seismic reflection data and well-established chronostratigraphy from five exploration wells. Seismic interpretations and correlations suggest four main evolutionary stages for the Late Jurassic – Paleogene sedimentary record, characterized by distinctive, diagnostic features at large (>1–10 km) to small (<100 m) scales: 1) initial turbidite systems developed between 160 and 125 Ma with extensive tributary channel networks along the upper continental slope that fed submarine channels and channel-levees further down-slope; 2) onset and growth of mixed systems at 125–78 Ma, characterized by a seaward progradation and NE migration of down-slope elongated mounded drifts and wide, U-shaped channels formed under potentially synchronous interactions between a SW-flowing bottom current and SE-directed turbidity flows; 3) shift of mixed systems at 78–50 Ma with SW migration of the mounded drifts and submarine channels, associated with a potential switch of the bottom current direction at 78 Ma, from SW towards NE; and 4) burial stage post-50 Ma, characterized by several stages of hemipelagic deposition followed by gully erosion at approximately 50, 40, and 35 Ma. The gradual transition from turbidite systems to fully developed mixed systems is associated with the tectonic and sedimentary background of the Nova Scotian margin during the Early to Late Cretaceous, as well as the establishment of a Cretaceous to Eocene paleoceanographic circulation. Comparisons with other ancient and modern mixed systems reveal similar morphological features (e.g., mounded drifts and submarine channels) formed under synchronous and asynchronous interactions between along- and down-slope processes. Their lateral distribution and vertical variability reflect a gradual change between the most influential process, from down-slope turbidity currents to along-slope bottom currents. Secondary depositional features along the mounded drifts, such as N–S oriented sediment waves, result from along-slope sediment redistribution and remobilization near the seafloor. Mixed depositional systems form unconventional plays and may become future targets for energy geosciences in a search for hydrocarbons or carbon capture and storage. Highlights: Cretaceous to Eocene mixed depositional systems are identified off Nova Scotia. Distinct morphological elements are recognized at different spatial scales. A gradual transition occurred between turbidite, mixed and contourite settings. Synchronous and asynchronous interactions between along- and down-slope processes. Basins and gateways reconfigurations affected the North Atlantic paleo-circulation.